Comparative Health Governance and Financing Reforms across Regional and International Health Policy Contexts Systems Workforce - Jessy Andre Mangaya Takke (Lembaga Edukasi Ilmiah Indonesia, 2026)
Introduction: Health governance and financing reforms are central to strengthening health systems and addressing persistent challenges related to service delivery, equity, and workforce performance across regions. Comparative analysis is essential to understand how different policy approaches influence reform outcomes in diverse national and international contexts. This study aimed to analyze the relationships between health governance reforms, health financing reforms, and health system and workforce performance within a comparative policy framework. Methods: A quantitative cross-sectional design was applied involving 50 respondents with experience in health policy, governance, financing, and workforce management. Data were collected using a structured questionnaire and analyzed using descriptive statistics and Pearson correlation tests. Results: The findings indicate that both health governance and financing reforms are positively associated with health system and workforce performance. Governance reforms demonstrated a stronger relationship with system outcomes than financing reforms, highlighting the importance of institutional coordination and accountability. Conclusion: Effective alignment of governance and financing reforms is critical for achieving resilient and equitable health systems. The study provides empirical evidence to support integrated policy approaches and offers a foundation for further comparative health policy research.